2013
DOI: 10.1111/ijcs.12023
|View full text |Cite
|
Sign up to set email alerts
|

Public face and private thrift in Chinese consumer behaviour

Abstract: The concept of face, or mianzi, is quite important in Chinese culture. We examine how public face and private thrift together affect Chinese consumer shopping behaviour based on the results of a survey of nearly 400 Chinese consumers under the age of 40. When a product is used in public or the behaviour occurs in a public place, Chinese consumers are typically willing to spend more money than if a product or service is used in a private place or at home. In addition, non-Chinese or Western brands do not mean m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…The above studies focused on collectivism/individualism as the dimension for examining consumers’ cultural differences. However, other studies suggested that consumers’ cultural difference can be tested with other concepts, for example face consciousness (Lin, Xi, and Lueptow, ; Qian, Abdur Razzaque, and Ah Keng, ; Zhou & Hui ), risk and uncertainty avoidance (Lim, Hu, Maynard, & Goddard, ; Vogt & Fesenmaier, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The above studies focused on collectivism/individualism as the dimension for examining consumers’ cultural differences. However, other studies suggested that consumers’ cultural difference can be tested with other concepts, for example face consciousness (Lin, Xi, and Lueptow, ; Qian, Abdur Razzaque, and Ah Keng, ; Zhou & Hui ), risk and uncertainty avoidance (Lim, Hu, Maynard, & Goddard, ; Vogt & Fesenmaier, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It reflects one's social selfesteem and the desire to be respected during interpersonal interactions (Ting-Toomey and Kurogi, 1998). As face describes one's wealth and prestige (Hwang, 1987;Zhang and Cao, 2010), people with strong face consciousness tend to pursue money and material wealth, regardless of how rich or poor, to enhance their reputation and social status (Wong and Ahuvia, 1998;Lin et al, 2013). Hence face makes the features of materialism stand out (Li and Su, 2007;Liao and Wang, 2009).…”
Section: Facementioning
confidence: 99%
“…While research has found that these Chinese traditional cultural values influence various consumer behaviours, such as customer satisfaction (Yau, 1994), online shopping (Wu et al, 2011), thrift and spending (Lin et al, 2013), purchase decisions (Liang and He, 2012) and gift giving (Yau et al, 1999;Joy, 2001;Qian et al, 2007), there is little research as to the effect of these values on materialism and desire for luxury products. While research has found that these Chinese traditional cultural values influence various consumer behaviours, such as customer satisfaction (Yau, 1994), online shopping (Wu et al, 2011), thrift and spending (Lin et al, 2013), purchase decisions (Liang and He, 2012) and gift giving (Yau et al, 1999;Joy, 2001;Qian et al, 2007), there is little research as to the effect of these values on materialism and desire for luxury products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, recent work has shown the significance beyond the Global North of classic theorisations of consumption, notably Veblen on the connections between status and conspicuous consumption, and of Bourdieu's (1984) highly influential account of distinction and taste in cultures of consumption (Hanser, 2008(Hanser, , 2010Gregson et al 2010;Podoshen et al 2011;Lin et al 2013).…”
Section: : Introductionmentioning
confidence: 99%